Student obesity prevalence and behavioral outcomes for the Massachusetts Childhood Obesity Research Demonstration project - Franckle, Rebecca L.; Ganter, Claudia (Obesity, 2017)
Objective To examine changes in prevalence of obesity and target health behaviors (fruit, vegetable, and beverage consumption; physical activity; screen time; sleep duration) among students from communities that participated in the Massachusetts Childhood Obesity Research Demonstration (MA-CORD) project compared to controls. Methods MA-CORD was implemented in two low-income communities. School-level prevalence of obesity among students in first, fourth, and seventh grades was calculated for the intervention communities and nine matched control communities pre and post intervention. Fourth- and seventh-grade students’ self-reported health behaviors were measured in intervention communities at baseline and post intervention. Results Among seventh-graders (the student group with greatest intervention exposure), a statistically significant decrease in prevalence of obesity from baseline to post intervention in Community 2 (-2.68%, P = 0.049) and a similar but nonsignificant decrease in Community 1 (-2.24%, P = 0.099) was observed. Fourth- and seventh-grade students in both communities were more likely to meet behavioral targets post intervention for sugar-sweetened beverages (both communities: P < 0.0001) and water (Community 1: P < 0.01; Community 2: P = 0.04) and in Community 2 for screen time (P < 0.01). Conclusions This multisector intervention was associated with a modest reduction in obesity prevalence among seventh-graders in one community compared to controls, along with improvements in behavioral targets.
Gesehen am 30.10.2018